Using of the Correction Schwarzschild radius Equation and Its Application of the Black Holes - Al-kubaisy, Majida H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study is a try to compare between the traditional Schwarzschild’s radius and the equation of Schwarzschild’s radius including the photon’s wavelength that is suggested by Kanarev for black holes to correct the error in the calculation of the gravitational radius where the wavelengths of the electromagnetic radiation will be in our calculation. By using the different wavelengths; from radio waves to gamma ray for arbitrary black holes (ordinary and supermassive).